Phytochemistry, pharmacology, toxicology and detoxification of Polygonum multiflorum Thunb.: a comprehensive review - Qian, Jiawen; Feng, Chenhang; Wu, Ziyang; Yang, Yuanmei; Gao, Xiangfu; Zhu, Lingyan; Liu, Yang; Gao, Yuancheng (Frontiers in Pharmacology, 2024)
Background Polygonum multiflorum Thunb. (PM), a kind of perennial plant, belongs to the genus Polygonum of the family polygonaceae.The dry root of PM (also called Heshouwu), is a traditional Chinese medicine, which has a series of functions and is widely used in clinic for hair lossing, aging, and insomnia. While, PM also has some toxicity, its clinical drug safety has been concerned. In this paper, the chemical components, toxic mechanisms and detoxification strategies of PM were reviewed in order to provide evidence for its clinical application. Materials and methods We conducted a systematic review of published literature of PM, including English and Chinese databases, such as PubMed, Web of Science, CNKI, and Wanfang. Results PM contains a variety of chemical compounds, including stilbenes, quinones, flavonoids, phospholipids, and has many pharmacological activities such as anti-aging, wound healing, antioxidant, and anti-inflammatory properties. The PE has certain therapeutic effect, and it has certain toxicity like hepatotoxicity, nephrotoxicity, and embryotoxicity at the same time, but.these toxic effects could be effectively reduced by processing and compatibility. Conclusion It is necessary to further explore the pharmacological and toxicological mechanisms of the main active compounds of PE.This article provides scientific basis for the safe clinical application of PM.